2018
DOI: 10.1177/0969776418795208
|View full text |Cite
|
Sign up to set email alerts
|

Bordering imaginaries and the everyday construction of the Mediterranean neighbourhood: Introduction to the special issue

Abstract: This special issue of European Urban and Regional Studies maps out a move from a strictly geopolitical to more socio-political and socio-cultural interpretations of the European Union’s (EU’s) ‘Mediterranean neighbourhood’. In doing this, the authors propose a dialogic understanding of neighbourhood as a set of ideas and imaginaries that reflect not only top-down geopolitical imaginaries but also everyday images, representations and imaginations. The introduction briefly summarizes conceptualizations of ‘neigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Yet, even though since the first representations of this area in the 1990s, its function of interface between Europe and the rest of the Mediterranean was highlighted, sometimes pointing out stronger links towards the Southern Mediterranean (Fig. 4), the reality is more complex and sensitive (Scott, Celata & Coletti, 2019), as we can see in the current developments in the area. system of relations with Northern Europe; c. opening towards the Mediterranean and beyond Source: Juan (1994, p.12).…”
Section: The Western Mediterranean: Macro-regional Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, even though since the first representations of this area in the 1990s, its function of interface between Europe and the rest of the Mediterranean was highlighted, sometimes pointing out stronger links towards the Southern Mediterranean (Fig. 4), the reality is more complex and sensitive (Scott, Celata & Coletti, 2019), as we can see in the current developments in the area. system of relations with Northern Europe; c. opening towards the Mediterranean and beyond Source: Juan (1994, p.12).…”
Section: The Western Mediterranean: Macro-regional Featuresmentioning
confidence: 99%
“…Moreover, several observers consider that the implementation of macro-regional cooperation is particularly challenging in such an unstable and discontinuous space (EP, 2015;Cugusi & Stocchiero, 2016, p.184;Scott et al, 2019). For instance the Mediterranean cross-border programme of the 2014-2020 Neighbourhood Policy has been delayed for political reasons and the first call for projects was only launched in July 2017.…”
Section: Tension Between Spatial Projections and Planning Policies: Wmentioning
confidence: 99%
See 1 more Smart Citation
“…A. Paasi revealed that the processes of social and political disintegration and integration often run in parallel: the social processes work to strengthen national identity and national sovereignty, contributing to the consolidation of borders; meanwhile, the political processes are aimed at finding common interests, liberalizing the border regime, and increasing bilateral contacts (Paasi and Prokkola 2008;Paasi 2009). The discovery of the interdependence between national border regimes and social perceptions has stimulated the study of public and institutional (that is, political) discourses about neighboring countries and regions (Newman and Paasi 1998;Prokkola 2009;Pfoser 2015;Konrad et al 2019;Scott et al 2019).…”
Section: The Theoretical Framework Of the Studymentioning
confidence: 99%
“…As part of elaborating a critical approach to interpreting the significance of illiberalism as a platform for V4 subregionalism, I take inspiration from political geography and regional study perspectives that challenge normative notions of Europeanization as a center-to-periphery diffusion of ideas and practices (Biebuyck and Rumford 2012;Moisio et al 2013). Furthermore, critical political geography has highlighted the significance of socio-spatial imaginaries such as border-making and regionalizing practices that are often driven by simultaneous contestations and affirmations of the European Union (Bürkner 2020;Ganesh and Froio 2018;Scott et al, 2019;Celata and Coletti 2019). In their explorations of the political geographies of Europeanization, Moisio et al (2013, 2) raised the issue that divisive imaginations of North-South difference emerging with the financial, debt, and more general Eurozone crisis have challenged "the fiction of European unity."…”
Section: Introductionmentioning
confidence: 99%